2016
DOI: 10.1148/radiol.2016151947
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation Rate at MR Imaging–guided Vacuum-assisted Breast Biopsy: A Multi-Institutional Retrospective Study of 1509 Breast Biopsies

Abstract: Purpose To assess the rate of underestimation of atypical ductal hyperplasia (ADH) and ductal carcinoma in situ (DCIS) at magnetic resonance (MR) imaging-guided vacuum-assisted breast biopsy and to explore the imaging, demographic, and histologic characteristics associated with lesion upgrade after surgery. Materials and Methods This retrospective study had institutional review board approval, and the need to obtain informed patient consent was waived. A total of 1509 MR imaging-guided vacuum-assisted biopsy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 40 publications
9
14
1
Order By: Relevance
“…Here, our study yields some interesting results: mass lesions seem to have a significantly higher malignancy rate than non-mass lesions (31% compared to 0%). This is in accordance with a large retrospective multi-institutional study showing that upgrades of ADH and DCIS diagnosed at MR-guided VAB are significantly associated with the presence of a mass on MR imaging [ 25 ]. Furthermore, our study indicates a higher malignant potential for smaller lesions ≤10 mm (PPV 35%) compared to lesions measuring 11–20 mm (PPV 23%) in case of MR-only lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Here, our study yields some interesting results: mass lesions seem to have a significantly higher malignancy rate than non-mass lesions (31% compared to 0%). This is in accordance with a large retrospective multi-institutional study showing that upgrades of ADH and DCIS diagnosed at MR-guided VAB are significantly associated with the presence of a mass on MR imaging [ 25 ]. Furthermore, our study indicates a higher malignant potential for smaller lesions ≤10 mm (PPV 35%) compared to lesions measuring 11–20 mm (PPV 23%) in case of MR-only lesions.…”
Section: Discussionsupporting
confidence: 91%
“…According to our experience, a multidisciplinary approach concerning the clinical risks of these cases should be provided. In this study, high-risk benign lesions were 19% of all lesions, concordant with the relevant literature (4%-21.5%) (19)(20)(21)(22)(23)(24)(25). Underestimation rate for high-risk benign lesions in this study was 21.4% (3/14), which was also similar with recent studies (19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 92%
“…Heller et al (21) reported that upgrade rates of high-risk lesions were significantly higher in cases with a history of malignant lesion in the same breast, recently diagnosed cancer, or history of high-risk lesion. No statistically significant relationship between lesion type or size and the underestimation rates was found in the literature ( 11,(19)(20)(21)(22)(23)(24)(25). Surgical excision is mandatory for high-risk lesions found at MRI-guided VABB, similar to other imaging-guided biopsy procedures.…”
Section: Discussionmentioning
confidence: 96%
“…For nearly 100% of respondents in Québec and France, the estimated performed number of weekly MRI-guided biopsies was reported as 5 or less, which may at first glance appear quite low. However, these numbers are in agreement with a recent multi-centric retrospective French and Swiss study reviewing 1709 MRI-guided biopsies collected over a 7-year period in nine institutions, representing an average number of 27 biopsies per year, per institution [19].…”
Section: Mri-guided Biopsies (Questions 5 and 6)supporting
confidence: 88%